PHYSICOCHEMICAL CHARACTERIZATION OF MUSCOVADO SUGAR USING DIFFERENT SUGARCANE VARIETIES AND STANDARDIZED LIME CONCENTRATION - Y. Teves, Karen (MATTER: International Journal of Science and Technology, 2016)
Muscovado is a specialty sugar that has a distinct taste and aroma making it unique and highly prized. Standardization of lime concentration was done using ten SRA and VMC HYVs. Mixed juices and processed muscovado were analyzed for yield and physicochemical properties. Clarified juice produced from ten sugarcane varieties and two lime concentrations – 500 ppm (T1) and 1000 ppm (T2) were processed into muscovado sugar. Sugarcane variety caused a significant variation in the pol, MC, SF, RS, sucrose, color, insolubles and yield of muscovado sugars. MC of muscovado ranged from 1.45 -6.8%, ash-1.33 to 2.72%, RS -1.91 to 5.2%, sucrose- 77.9 to 92.97%, color - 8,122 to 39, 567 I. U. and insolubles- 0.2 to 1.26%. T2 muscovado of VMC 84-524 obtained the highest sugar yield of 11.1%. Findings showed that Phil 7464 is the right variety when using either 500 or 1000 ppm lime to obtain high pol muscovado. To process muscovado of lower MC and SF, Phil 99-0925 can be used at 500 ppm while Phil 7464 and VMC 87-95 at 1000 ppm. For low ash and high sucrose, at either 1000 or 500 ppm, Phil 7464 is most ideal. At 500 ppm, Phil 99-0925, VMC 87-95 and Phil 7464 can be used. For low RS and insoluble, VMC 86-550, Phil 2001-0295 and Phil 99-1793 at 500 ppm can be utilized while 7464 and Phil 99-1793 at 1000 ppm. For high sucrose and sugar yield, Phil 99- 0925, VMC 84-524 and VMC 86-550 at 500 ppm is appropriate and Phil 7464 at 1000 ppm. Either 500 or 1000 ppm lime concentration at specific varieties can be used to obtain quality muscovado. The six most suitable varieties to use for muscovado processing are; Phil 7464, VMC 84-524, VMC 86-550, VMC 87-95, Phil 99-0925 and Phil 2001-0295.